2006
DOI: 10.1542/peds.2004-2809
|View full text |Cite
|
Sign up to set email alerts
|

Project Universal Preschool Vision Screening: A Demonstration Project

Abstract: OBJECTIVES. Visual disorders among preschool-aged children are common, yet screening is infrequent. The purpose of this project was to implement the vision screening recommendations proposed by the Maternal and Child Health Bureau and National Eye Institute Vision Screening in the Preschool Child Task Force: monocular visual acuity and stereopsis testing.METHODS. Four sites fully participated in the implementation of the task force recommendations with 3-and 4-year-old children. Two of the sites worked with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…[71] The results showed that significantly more children were referred and treated following a communitybased screen than a primary care practice screen. Unfortunately, the authors could only speculate as to why this occurred, suggesting that perhaps lay screeners were more conservative, or that nurses and doctors lacked an understanding of the systematic screening of young children.…”
Section: Preschool Age (3-6 Years)mentioning
confidence: 99%
See 1 more Smart Citation
“…[71] The results showed that significantly more children were referred and treated following a communitybased screen than a primary care practice screen. Unfortunately, the authors could only speculate as to why this occurred, suggesting that perhaps lay screeners were more conservative, or that nurses and doctors lacked an understanding of the systematic screening of young children.…”
Section: Preschool Age (3-6 Years)mentioning
confidence: 99%
“…The studies reported that orthoptists were effective screeners; [68] that health visitors were just as effective as orthoptists; [27] that nurses achieved better results than teacher questionnaires, [57] similar results to optometrists, [69] and results of sufficient specificity and sensitivity to be considered primary screeners [10]; that parents were effective administrators of vision tests in the home, [70] and that referral and treatment rates differed substantially between lay screeners and primary care practitioners, although little information was provided as to why this was the case. [71] The final non-randomised controlled trial, examining screening in children aged six years and over, concluded that nurses could perform the role of primary screener with appropriate training from other eye health professionals. It was reported that training was particularly required for the detection of strabismus [72] and it was hoped that this training would address the high false positive rate obtained by the nurses in the study.…”
Section: Overall Summary -Screener Characteristicsmentioning
confidence: 99%
“…12 Barriers to primary care vision screening may include deficiencies in reimbursement, incomplete primary care education in screening, and limitations of the testing techniques themselves. 12,13 Problems have been reported with primary care screening related to screening penetrance, testability, and referral. 13,14 Evidence for the real-world effectiveness of preschool vision screening in the primary care setting is lacking.…”
mentioning
confidence: 99%
“…12,13 Problems have been reported with primary care screening related to screening penetrance, testability, and referral. 13,14 Evidence for the real-world effectiveness of preschool vision screening in the primary care setting is lacking. 15 Therefore, the Children's Eye Foundation (CEF), the charitable foundation of AAPOS, established its See by Three program with the goal of significantly reducing amblyopia in young children.…”
mentioning
confidence: 99%
“…1 Visual plasticity is limited to a critical early period in life, and preschool vision screening programs or recommendations have been discussed in several articles. [2][3][4] In addition, uncorrected refractive error, such as myopia, recently has been identified as a significant visual problem in children. 5 Myopia is also a major public health concern in Taiwan, which has a 20%, 61%, and 81% rate of prevalence among schoolchildren ages 7, 12, and 15 years, respectively.…”
mentioning
confidence: 99%